Analisis Semiotika Rolland Barthes Pada Lagu Qaliilu Aqlin Karya Band Alfarabi Musik" - Anggraini, Dwi; Walidin, Muhammad; Albab, Ulil (TAMADDUN, 2024)
This research employs a semiotic approach by Roland Barthes on the song "Qaliilu Aql." The aim of this study is to analyze the signs and meanings contained in the lyrics of "Qaliilu Aql," including both literal meanings and implied meanings, referred to as denotative and connotative meanings, as well as mythological messages. The research questions in this study are: first, what are the forms of denotative and connotative meanings in the song "Qaliilu Aql"? Second, what is the form of the myth in the song "Qaliilu Aql"? The method used in this study is qualitative descriptive, utilizing data collection techniques such as observation, reading, and note-taking. The researcher presents the data in both formal and informal formats. The results of this study indicate that there are 3 denotative meanings, 3 connotative meanings, and 3 mythological messages found in the first, second, and seventh stanzas.